New Neotropical species of Marilia Müller (Trichoptera: Odontoceridae) - Camargos, Lucas M.; Pes, Ana Maria; Hamada, Neusa (Zootaxa, 2020)
Five new species of the caddisfly genus Marilia Müller 1880 are described from the Neotropics, Marilia cabocla sp. nov., Marilia caipira sp. nov., Marilia cunhaporanga sp. nov., Marilia manicorei sp. nov., and Marilia muelleri sp. nov. Larvae and pupae of new species are also described, in addition to the immature stages of M. fasiculata Banks 1913 and M. huamantincoae Dumas & Nessimian 2009; an updated description of M. siolii Marlier 1964 male is provided. This work raises the number of species of this genus from 46 to 51 for the Neotropical Region.